The Essence of English as a Global Connector (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
English has become a crucial global connector, enabling communication across diverse cultures and regions. This article examines the role of English in accessing information, facilitating international business and diplomacy, and promoting cultural exchange. With its dominance in education, technology, and media, English is essential for navigating the globalized world, making it a vital tool for gaining a broader, global perspective.